Educating deaf students : from research to practice - Marschark, Marc; Lang, Harry G.; Albertini, John A. (John Anthony), 1945- (Oxford University Press, 2002)
"Over the past decade there has been a significant increase in interest from educators and the general public about deafness, special education, and the development of children with special needs. The education of deaf children in the United States has been seen as a remarkable success story around the world, even while it continues to engender domestic debate." "In Educating Deaf Students: From Research to Practice, Marc Marschark, Harry G. Lang, and John A. Albertini set aside the politics, rhetoric, and confusion that often accompany discussions of deaf education. Instead they offer an accessible evaluation of the research literature on the needs and strengths of deaf children and on the methods that have been used - successfully and unsuccessfully - to teach both deaf and hearing children."--Jacket